Poaceascoma aquaticum sp. nov. (Lentitheciaceae), a new species from submerged bamboo in freshwater - Luo, Zong-Long; Bahkali, Ali H.; Liu, Xiao-Ying; Phookamsak, Rungtiwa; Zhao, Yong-Chang; Zhou, De-Qun; Su, Hong-Yan; Hyde, Kevin D. (Phytotaxa, 2016)
Poaceascoma aquaticum sp. nov. (Lentitheciaceae) was found on decaying bamboo submerged in a freshwater stream in northern Thailand. The new species is introduced based on its unique morphology and phylogeny. Poaceascoma aquaticum is characterized by black, semi-immersed or erumpent, papillate ascomata, bitunicate, cylindrical to cylindric-clavate, short pedicellate asci and filiform, pale brown to brown ascospores. Phylogenetic analyses of combined LSU, SSU and RPB2 sequence data shows that Poaceascoma aquaticum forms a robust clade with P. helicoides in the family Lentitheciaceae (Pleosporales). Poaceascoma aquaticum is described, illustrated and compared with related taxa.